La scena originaria: argomentazione, retorica e medicina a partire dal Gorgia di Platone - Serra, Mauro (Rivista Italiana di Filosofia del Linguaggio)
Starting from a well-known scene of Plato’s Gorgias, where the sophist claims the need for the doctor to resort to his art, that is rhetoric, the paper tries to reconstruct the relationship between rhetoric, argumentation and medicine in the preplatonic age. Unlike the image provided in Plato’s Gorgias scene, this relationship is much more complex. It focuses on two main aspects: 1) how to acquire knowledge of what escapes direct observation; 2) how soul and body interact in human action.